Audience Reception of Celebrity Private Sphere through Janji Suci Raffi & Gigi - Natasya N. Mandagi; Nuriyatul Lailiyah, S.Sos, M.I.Kom (Interaksi Online, 2016)
The emergence of reality show programs on various television stations became a unique phenomenon to the community. Trans TV station became one of the famous private television that has many programs in television reality show, one of which is Janji Suci Raffi & Gigi. The program presents stories about the private lives of households Raffi Ahmad and Nagita Slavina, as well as the story of the people around them. The purpose of this study is to determine audience reception of the private sphere celebrity audience through Janji Suci Raffi & Gigi. This research is using descriptive-qualitative with reception analysis by Stuart Hall. The theory used receptions Analysis Stuart Hall. Data collection techniques performed by using in-depth interview to four informants which is audience of Janji Suci Raffi & Gigi. The outcome from this research showed that the audience of Janji Suci Raffi & Gigi viewing entertainment programs such as serving personal life of Raffi Ahmad and Nagita Slavina and the people around them. Audience actively interpret the message on Janji Suci Raffi & Gigi dynamic and change according to the displayed context and background of each. Audience reception to the celebrity’s private sphere, all matters outside his profession as an artist, it could be households, personal conflicts, and other personal life. So that the pro and cons of the feasibility of a private space in the public airing television. Some informants agree some do not agree with that. Factors that influence the differences in the position of the informant is the educational background, culture, and gender.